The Spanish domain - Gibb, Hugh. ([Manila Felta Book Sales], 1981)
Shows how the Spaniards brought and spread Christianity in the Philippines.
Edited by Mel Roberts.
Keywords: Christianity -- History. -- Philippines; Christianity -- Origin. -- Philippines; Philippine history; Religion